Correlation of Interpersonal Intelligence with Biology Learning Outcomes of Students in Senior High School - Listiana, Tia; Novallyan, Devie; Chatib, Muhsin; Salahuddin; Sari, Defita Permata (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2025)
In learning biology, there are many topics that require group work, such as practicum in the laboratory, observation in the field, or discussion of more complex concepts. In this process, interpersonal intelligence becomes one of the important factors in supporting the biology learning process. This study aims to prove whether or not there is a correlation between interpersonal intelligence and students' biology learning outcomes in high school. This research is a quantitative study with a correlational research design. The research was conducted at Ar-Riyadl High School with a total research sample of 30 students. The instrument used was a questionnaire for the independent variable (interpersonal intelligence) and documentation of the Final Semester Assessment (PAS) of the 2023/2024 school year for the dependent variable (biology learning outcomes). Data analysis to test the research hypothesis using Pearson Product Moment correlation analysis. The results showed that there was a correlation between interpersonal intelligence and students' biology learning outcomes in senior high school. This can be seen in the value of r count (0.662) > r table (0.361) and the significance value (0.662) > 0.05 which means Ho is rejected and Ha is accepted. So it can be concluded that the research hypothesis that has been formulated can be accepted, namely that there is a correlation between interpersonal intelligence and students' biology learning outcomes in senior high school.